Upaya Preventif Masyarakat Srimenanti dari COVID-19 melalui Pembagian Masker dan Handsanitizer - Adisyahputra Adisyahputra; Robby Gus Mahardika; Gita Afriza (Fakultas Teknik, Universitas Bangka Belitung, 2021)
Indonesia is currently being shaken by the COVID-19 pandemic, which has infected thousands of people and even died. The government has given an appeal to the community to reduce the spread of the COVID-19 virus. However, not many people have complied with the government's appeal. Especially in Srimenanti Village, very few people know how dangerous the COVID-19 virus is. Therefore it is necessary to understand the health protocol for breaking the COVID-19 chain. Based on these problems, the authors carry out community service through Real Work Lecture (KKN) activities with the theme COVID-19, the method used to support public safety against COVID-19, namely in the form of distribution of masks and hand sanitizers also educating the public about COVID-19. The results show that people who previously did not care about the pandemic are currently progressing and are more concerned about themselves and those around them. Evidenced by always using a mask and hand sanitizer when leaving the house.